Developing Encyclopaedia Media on Form and Function of Plant to Train Elementary Students' Critical Thinking Skill - Erawati, Yeny; Raharjo, Raharjo; Azizah, Utiya (International Journal for Educational and Vocational Studies, 2020)
This study aims to develop effective, feasible, and valid encyclopedia media on form and function of plant to train fourth-graders’ critical thinking skills in the elementary school. This study was research and development based on Borg and Gall theory and Research (R& D) model. Data were collected using observation, questionnaires, and tests and analyzed using media validity and reliability, student activity, implementation of lesson plans, and tests of critical thinking skills. After that, the media was validated by experts. The results of the expert validation showed that the Encyclopedia media was valid for use. Furthermore, the media was tested on fourth-graders of SDN KERTAJAYA V / 211 Surabaya using One Group Pretest-Posttest Design. The limited scale trial results showed (1) the validation of the developed Encyclopedia media were 96% valid categories, (2) the developed media were tested in term of lesson plan implementation were 94% with well-implemented category and student activities were suitable to Discovery Learning model, (3) the effectiveness of the Encyclopedia media in terms of students’ critical thinking skills tests showed that average N-Gain was 0.75 (high) and positive response of 97% was given by students. Therefore, it can be concluded that the Encyclopedia media on Form and Function of Plant is feasible to train Critical Thinking Skills of Elementary School Students.